Traveling wave distortion of MEMS ultrasonic motor induced by anisotropic elasticity. (15th April 2023) - He, Jiangbo; Chen, Yu; Cao, Binlei; Li, Xiaoshi; Yang, Tianyu; Hu, Zongda; Ran, Longqi; Zhou, Wu
Abstract: It is crucial to study the problem of traveling wave distortion due to its severe effect on the stability and efficiency of traveling wave ultrasonic motors (TWUM). In this study, the anisotropic elasticity as a new factor causing the traveling wave distortion in MEMS TWUM was considered, and an electromechanical model considering the effect of anisotropic elasticity was established to evaluate the distorted traveling wave. Initially, the orthogonal modes of the stator were investigated using finite element simulation, and the orthogonal modes' two defects induced by the anisotropic elasticity were observed, which included modal splitting and shape distortion. Subsequently, the electromechanical model was established based on the defective orthogonal modes using Hamilton's principle and classical laminated plate theory. Additionally, the effect of modal splitting and shape distortion on the traveling wave distortion was investigated based on the electromechanical model. It demonstrated that B13 was the optimal orthogonal mode for the high-quality traveling wave. Finally, MEMS TWUMs were fabricated and tested to verify the theoretical results. The test results were obtained using a laser Doppler vibrometer, and it was observed that the traveling wave produced from B13 was optimal. The test results of rotational speed measured using a high-speed camera also verified that B13 was the optimal orthogonal mode for the traveling waves.